Study on the optimum pressure controllability of PID tuning by using different tuning rules: article - Zolkapali, Siti Norhana Fatehah; Ishak, Abdul Aziz (2017)
This study is carried out to determine the optimum pressure controllability by using various tuning rule. There are several analyses conducted in this study which are open loop analysis and closed loop analysis. The method used for open loop test is Reformulated Tangent Method while the different tuning rules used is Ziegler-Nichols; Cohen-Coon; Chien, Hrones and Reswick (CHR) and Takahashi. Next, closed loop analysis is carried out by performing performance tests and fine tuning. This performance tests are conducted to observe and investigate the best and efficient tuning rule when the set point and load disturbance is change [1]. The controller that has minimum settling time and peak overshoot and less error will be considered as the best controller and efficient controller [4].